Tissue-specific abscisic acid, jasmonic acid, and cytokinins dynamics during on-tree ripening of ‘Rojo Brillante’ persimmon - Vilhena, Nariane Q.; Alamar, M. Carmen; Collings, Emma R.; Moreno, Ana; Salvador, Alejandra (Springer, 2026)
This study investigated the tissue-specific dynamics of abscisic acid (ABA) and its metabolites, jasmonic acid (JA), and cytokinins (CK) in the apical and basal flesh and the calyx of ‘Rojo Brillante’ persimmon during fruit development and on-tree ripening. Flesh ABA and 7-OH-ABA were high at the beginning of fruit development (60 days after full bloom, DAFB) and showed a transient accumulation at 150–180 DAFB, which was associated with ripening-related changes such as increased external color and firmness loss. The decline in ABA levels at the last ripening stages coincided with the increase in its oxidized metabolites (PA and DPA), indicating active ABA catabolism during late maturation. JA remained low in the flesh until 150 DAFB but rose thereafter in the apical region, suggesting a tissue-specific contribution to texture modulation. CK levels, mainly, tZ and iP were related to fruit growth. Moreover, the early increase in tZ was accompanied by decreases in ABA and 7-OH-ABA, suggesting antagonistic crosstalk between CK and ABA. In the calyx, the peak of ethylene and CO₂ at 120 DAFB coincided with the maximum accumulation of ABA and 7-OH-ABA in this tissue and was linked to the onset of fruit ripening. In contrast to flesh, JA levels in the calyx were markedly high during early development and declined progressively through maturation. CK in the calyx followed distinct patterns throughout fruit maturation. Together, these findings provide a coherent framework for understanding persimmon development and maturation and establish a basis for optimizing harvest timing and postharvest management.
Keywords: Diospyros kaki thunb; Hormonal profile; Fruit development; Calyx; 30 Agricultural, Veterinary and Food Sciences; Pediatric Research Initiative; Plant Biology & Botany; 3004 Crop and pasture production; 3008 Horticultural production; 3108 Plant biology